2016
DOI: 10.21831/reid.v2i1.8307
|View full text |Cite
|
Sign up to set email alerts
|

Model of affective assessment of primary school students

Abstract: This study aims to develop an instrument of affective assessment to measure the social competence of elementary school students in the learning process in schools. This study used the development model of Borg & Gall's approach which was modified into five phases, including the need analyses, developing draft of the product conducted by experts, developing an affective assessment instrument, trying out the affective assessment instrument conducted by teachers of primary education in Yogyakarta, and the dissemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…The evaluation instrument items development that could be used to measure the three domains was also in accordance with the research result that was conducted by Rovai et al [17] by showing the development and validation of instruments to obtain instruments that could be used to measure the the learning process effectiveness in affective, cognitive and psychomotor domains. Other researches which also in principle reinforce Rovai et al's statement about the instrument items development to measure several educational domains were research that was conducted by Saptono, Suparno, and Najah [18]and also research by Syamsudin, Budiyono, and Sutrisno [19] which basically showed the valid and reliable instruments development to measure the learning process in the affective domain. The research that was conducted by Paidi et al [20] and also Großschedl, Mahler, and Harms [21] strengthen statements about the evaluation instrument items development in the cognitive domain.…”
Section: Final Itemsmentioning
confidence: 72%
See 1 more Smart Citation
“…The evaluation instrument items development that could be used to measure the three domains was also in accordance with the research result that was conducted by Rovai et al [17] by showing the development and validation of instruments to obtain instruments that could be used to measure the the learning process effectiveness in affective, cognitive and psychomotor domains. Other researches which also in principle reinforce Rovai et al's statement about the instrument items development to measure several educational domains were research that was conducted by Saptono, Suparno, and Najah [18]and also research by Syamsudin, Budiyono, and Sutrisno [19] which basically showed the valid and reliable instruments development to measure the learning process in the affective domain. The research that was conducted by Paidi et al [20] and also Großschedl, Mahler, and Harms [21] strengthen statements about the evaluation instrument items development in the cognitive domain.…”
Section: Final Itemsmentioning
confidence: 72%
“…The full description of the cross-tabulation process can be seen in Table 6. 3,4,5,6,7,8,9,10,12,13,14,15,16,17,18,19,20,21,22,23,24,25,27,28,29,31,32,33,34,35,36,37,38,39,40,41,42,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,…”
Section: Trial Of Tri Kaya Parisudha-based Countenance Evaluation Instrumentmentioning
confidence: 99%
“…Likewise, social education habitually practiced in the family to make one frugal, dislike vain deeds or conditions, give help easily, and have empathy to someone suffering is also reinforced by religion education in school. Education of the family model works in synergy with education of the school model (Syamsudin, Budiyono & Sutrisno, 2016). The research finding showed that peer assessment and self-assessments were able to improve the interpersonal communication skill of accounting students.…”
Section: Resultsmentioning
confidence: 92%
“…Pendidikan dinilai telah mencapai tujuan apabila lulusan yang dihasilkan mampu berdaya saing dengan mutu lulusan yang lain [3]. Pendidikan memegang peranan penting dalam kehidupan manusia [4]. Menurut [5], tujuan pendidikan nasional adalah untuk mengembangkan potensi peserta didik sehingga mereka menjadi individu Indonesia dengan iman dan takut akan Tuhan, moral yang mulia, kesehatan yang baik, pengetahuan yang hebat, kompetensi, kreativitas, dan kemandirian, dan menjadi individu yang demokratis dan warga negara yang bertanggung jawab.…”
Section: Pendahuluanunclassified